2020
DOI: 10.1016/j.beproc.2019.104026
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific patterns of minimal compensation of care during and after short term mate removal in biparental blue tits

Abstract: Early theoretical models predicted that over evolutionary timescales, changes in effort by one biparental parent should result in incomplete compensation by the other. Empirical studies, however, report responses ranging from no compensation through to complete compensation which may mean that parents respond to each other's efforts over short time scales, as predicted by some recent theoretical models. Few studies have examined behavioural changes over short time periods which mimic the onset of reduced effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…This prediction of ‘partial compensation’ has been tested empirically via experimental manipulation of partner's behaviour in a number of bird species [ 12 ]. These studies found substantial variation in the direction and magnitude of this compensatory response (for a summary on bird species see [ 13 ]), attributable to differences in the experimental set-ups [ 12 , 14 ], species [ 13 ], sexes [ 12 , 13 ] and parental tasks [ 15 , 16 ]. However, these studies have mostly explored variation in compensatory behaviour in terms of among-individuals (population mean) responses and have overlooked within-individual variation in responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This prediction of ‘partial compensation’ has been tested empirically via experimental manipulation of partner's behaviour in a number of bird species [ 12 ]. These studies found substantial variation in the direction and magnitude of this compensatory response (for a summary on bird species see [ 13 ]), attributable to differences in the experimental set-ups [ 12 , 14 ], species [ 13 ], sexes [ 12 , 13 ] and parental tasks [ 15 , 16 ]. However, these studies have mostly explored variation in compensatory behaviour in terms of among-individuals (population mean) responses and have overlooked within-individual variation in responsiveness.…”
Section: Introductionmentioning
confidence: 99%